2014
DOI: 10.1016/j.intermet.2014.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cr segregation to C11b/C40 lamellar interface in (Mo,Nb)Si2 duplex silicide: A phase-field study to bridge experimental and first-principles investigations

Abstract: a b s t r a c tCr segregation at lamellar interfaces in the MoSi 2 /NbSi 2 duplex silicide was examined using a newly developed phase-field model to elucidate the mechanism of interfacial segregation, which is believed to improve the thermal stability of lamellar structures as well as creep resistance. This is because lamellar structures can improve the high-temperature strength, and the stabilization of the lamellar structures improves creep resistance. The model takes into account the segregation energy dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Gaussian functions are used to interpolate the energies of Cr atoms on the atomic plane to the position between the atomic layers smoothly. In our previous study, it was clarified that the Cr segregation at the lamellar interface was found to be the segregation energy rather than the relaxation of the lattice misfit [13].…”
Section: Chemical Energymentioning
confidence: 96%
See 4 more Smart Citations
“…Gaussian functions are used to interpolate the energies of Cr atoms on the atomic plane to the position between the atomic layers smoothly. In our previous study, it was clarified that the Cr segregation at the lamellar interface was found to be the segregation energy rather than the relaxation of the lattice misfit [13].…”
Section: Chemical Energymentioning
confidence: 96%
“…Finally, f seg ðc Cr ; /Þ is the segregation energy function, which represents the chemical energy due to the interaction between the additive Cr atoms and the atomic layers is the diffuse interface. The details of the segregation energy function was described in the previous paper [13]. Here, only the essentials of the segregation energy is described.…”
Section: Chemical Energymentioning
confidence: 99%
See 3 more Smart Citations